The Functional Value of Attributive Phrases in Legislative Texts in English - HAKOBYAN, ANNA (Bulletin of Yerevan University B: Philology, 2021)
In this article an attempt is made to reveal the main factors which condition the wide use of “noun + of + noun” phrases, and the almost lack of the other two types of attributive phrases typical of English, namely, “noun + noun” and “noun genitive + noun’’ in legislative texts. It is argued that the above mentioned is partly accounted for by the requirements of the grammatical norms of English but mainly by the tendency to emphasize the meaning of the utterance and avoid ambiguity.